Quantitative Approach to Fish Cytogenetics in the Context of Vertebrate Genome Evolution - Borůvková, Veronika; Howell, W Mike; Matoulek, Dominik; Symonová, Radka (Genes, 2021)
Our novel Python-based tool EVANGELIST allows the visualization of GC and repeats percentages along chromosomes in sequenced genomes and has enabled us to perform quantitative large-scale analyses on the chromosome level in fish and other vertebrates. This is a different approach from the prevailing analyses, i.e., analyses of GC% in the coding sequences that make up not more than 2% in human. We identified GC content (GC%) elevations in microchromosomes in ancient fish lineages similar to avian microchromosomes and a large variability in the relationship between the chromosome size and their GC% across fish lineages. This raises the question as to what extent does the chromosome size drive GC% as posited by the currently accepted explanation based on the recombination rate. We ascribe the differences found across fishes to varying GC% of repetitive sequences. Generally, our results suggest that the GC% of repeats and proportion of repeats are independent of the chromosome size. This leaves an open space for another mechanism driving the GC evolution in vertebrates.
Keywords: cytogenetika; rekombinace genetická; molekulární evoluce; Chromosomes; ptáci; GC-biased gene conversion; Birds; Recombination, Genetic; repetitivní sekvence nukleových kyselin; ryby; Evolution, Molecular; obratlovci; zastoupení bazí; genom; Genome; Vertebrates; zvířata; Base Composition; Cytogenetics; Fishes; Repetitive Sequences, Nucleic Acid; chromozomy; microchromosomes; Animals; linkage group; GC content; chromosome size